Pengaruh Hasil Pembelajaran Akidah Akhlak terhadap Etika Berbusana Muslimah di Luar Sekolah Siswa Kelas VIII MTs Besilam Babussalam - Diani Syahfitri; Trimerida Eka Putri (EduInovasi: Journal of Basic Educational Studies, 2021)
This study aims to answer questions in the formulation of the problem which include: (1) how are the learning outcomes of Aqidah Akhlak at MTs Besilam Babussalam School? (2) How is the ethics of Muslimah dress outside the school for the students of MTs Besilam Babussalam? (3) How is the effect of Aqidah Akhlaq learning outcomes on Muslimah Dress Ethics outside of school for Class VIII students of MTs Besilam Babussalam? The type of research that is used is the study of quantitative by using analysis of statistical product moment . To answer the formulation of the problem first and second researcher using a formula percentage, to research that to three researchers using the formula product moment . Meanwhile, for data collection using questionnaires, documentation and interviews. This research was conducted by taking a sample of 22 students from 80 total students. From this study, it can be seen that the ethical problem of dressing outside of school with the product moment formula , (1) learning outcomes of moral aqidah in Class VIII students of MTs Besilam Babussalam are classified as very good with 80% results from the range of 76% - 100%. (2) the ethics of Muslimah dress outside of school Class VIII students of MTs Besilam Babussalam are classified as quite good with results of 50% from the range of 26% - 50%. (3) Results Learning Aqeedah Morals memimliki influence on Ethics Dressed Muslimah in Outside School Students Class VIII MTs Besilam Babussalam. This was proved by Ha accepted and H0 is rejected with t arithmetic amounting from t table ie, Thitung > Ttabel = 7.3935> 2.07387.